Water Ontologies and Hydrosocial Perspective: New Approaches for Understanding Water Controversies of the Ing River Basin, Northern Thailand - Surimas, Thianchai (วารสารบัณฑิตแสงโคมคำ, 2024)
This research illustrates, through a hydrosocial perspective, how political contestation between different networks of actors reflected the meanings, values, and water ontologies. This research employs ethnography to study networks of actors involved in controversies over the hydraulic infrastructure project in the Ing River Basin. The network of project proponents, including a state-led hydraulic institution, experts, and other actors, see Water as merely a natural resource for economic development. The proponents reduce water to its materiality and physical dimensions. Water is tied with the idea of development that values large-scale infrastructure, and top-down bureaucratic management embodied scientific knowledge in controlling water, mainly for economic purposes. Meanwhile, project opponents, including civil society organizations, environmental NGOs, and some communities understand water as living. Living water is produced through Thai Baan research, ecological campaigns and ceremonial practices that show rivers as sacred. Living water is socially, environmentally, and culturally embedded and more than a resource for exploitation. This paper argues that water-related conflicts in the Ing River Basin not only reflect how water is managed but are also rooted in such ontological differences. Different networks produced different versions of water. Therefore, understanding water ontologies through a hydrosocial lens could provide a new perspective on water-related conflicts and controversies.